Clinicoepidemiological study of pre malignant and malignant lesions among patients attending the dermatology OPD in a tertiary care centre in Puducherry: a retrospective cross-sectional study - M., Trishna Vaishali; P., Nithiyaa; J., Sheron Christin Armel (International Journal of Research in Dermatology, 2025)
Background: The growing prevalence of skin cancer worldwide can be understood as the result of increased exposure to ultraviolet radiation. Fitzpatrick skin type 1 and 2 are at higher risk. They are poorly studied in Asians. Skin cancers accounts for 20%-30% of neoplasms in Caucasians and 2%-4% in Asians. Three million cases of non-melanoma skin cancer and 132 thousand melanomas are diagnosed worldwide every year. The aim of the study is to study the profile of patients with premalignant and malignant skin lesions visiting the dermatology OPD in Puducherry for a period of 3 years. Methods: Case records of 57,316 patients were studied. 82 case records of premalignant and malignant skin lesions were reviewed and analysed using SPSS software. The prevalence was calculated and also their distribution among age, gender and race was analysed. Results: 82 cases with 93 premalignant and malignant skin lesions were recorded. 77.4% (n=72) were premalignant lesions and 22.5% (n=21) were malignant lesions. The commonest premalignant lesion was leukoplakia (n=38, 52.78%) followed by actinic Keratosis (n=31, 43.05%), keratoacanthoma (n=2, 2.78%) and Bowens disease (n=1, 1.39%). The commonest malignant tumor in the study was basal cell carcinoma (n=12, 57.14%), followed by squamous cell carcinoma (n=9, 42.86%). There were no melanomas or lymphomas reported during the study period. Conclusions: The index of suspicion for the atypical presentations and earlier identification of the premalignant and malignant skin lesions can aid in the selection of appropriate treatment modality and thereby reducing their associated morbidity and mortality.